CONSUMER PROTECTION IN INTERNET SALES– DEGREE OF HARMONIZATION WITH THE EUROPEAN UNION LAW - Ranđelović, Dragana; Ljajić, Samir (The European Journal of Applied Economics, 2017)
In this paper the authors will strive to answer some general questions regarding the concept, significance and goals of the harmonization of contract law. Given the actuality and mass state of Internet sales, questions and issues of consumer protection will be set within the boundaries of this narrow field of contract law. In the central part of the paper, the authors will present the most important regulations governing this area both in the European Union and Serbia, as well as the degree of their harmonization. They will also attempt to provide answers to some basic questions and issues which customers face when making on-line purchases. The Republic of Serbia has passed a set of laws which comply with the requirements and standards of the European Union. However, it is necessary to continuously conduct the process of education not only of employees in state services and traders, but also consumers in order to raise awareness about the significance and benefits of e-commerce, and above all, customer protection.
Keywords: Internet sales; European Union; contract; consumer protection